Pengembangan Media Pembelajaran Komik Digital Pada Materi Dongeng Untuk Meningkatkan Keterampilan Membaca Siswa Kelas II Sekolah Dasar - Maya Urva; Bunga Mulyahati; Ronald Fransyaigu (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research examines the creation, validation, practicality, and effectiveness digital comic media designed to improve reading skills in second-grade students. Employing the ADDIE-based Research and Development (R&D) approach, the study involved one teacher, 23 students from SD Negeri Suka Jadi, and experts in materials, language, media, and assessment. Data were obtained through observations, interviews, questionnaires, and tests, and analyzed qualitatively. The development process involved five consecutive stages: analysis, design, development, implementation, and evaluation. The results demonstrate that. (1) validity achieved 90.18% (“very valid”), (2) practicality reached 85.33% (“very practical”), and (3) effectiveness testing showed a significant improvement (p < 0.05) Between the pretest and posttest, the average N-Gain was 0.5529 (moderate), indicating that the media is valid, practical, and moderately effective in improving reading proficiency.